2019
DOI: 10.31083/j.jin.2019.03.186
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of quetiapine on cognitive impairment associated with 5-HT1A presynaptic receptor involved schizophrenia

Abstract: The cognitive impairment associated with schizophrenia is highly prevalent and affects the overall functioning of subjects. The stimulation of the serotonin 1A receptor is a primary characteristic of some atypical antipsychotic drugs. We measured the levels of cognitive impairment using the Morris water maze test and protein kinase A activity in hippocampal neurons on presynaptic and postsynaptic serotonin 1A receptors to investigate the effect of dizocilpine-induced cognitive impairment associated with atypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The present results suggest that the presynaptic function of 5-HT 1A receptors may be important for the inhibition of hyperactivity in DD mice. Previous studies demonstrated the importance of the presynaptic function of 5-HT 1A receptors rather than their postsynaptic functions for the treatment of a low level of social interaction, anxiety, and cognitive dysfunction [23,24]. Thus, presynaptic 5-HT 1A receptors may also play an important role in improving PSDD.…”
Section: Discussionmentioning
confidence: 99%
“…The present results suggest that the presynaptic function of 5-HT 1A receptors may be important for the inhibition of hyperactivity in DD mice. Previous studies demonstrated the importance of the presynaptic function of 5-HT 1A receptors rather than their postsynaptic functions for the treatment of a low level of social interaction, anxiety, and cognitive dysfunction [23,24]. Thus, presynaptic 5-HT 1A receptors may also play an important role in improving PSDD.…”
Section: Discussionmentioning
confidence: 99%
“…It decreases the Bcl-XL/Bax ratio in the posterior cingulate cortex, ameliorating cognitive impairment and brain apoptotic processes. The drug has reached phase IV clinical trial [ 143 ]. Lecozotan, a selective 5HT1A receptor antagonist, shows increased learning and memory in rats by stimulating the release of glutamate and acetylcholine in the hippocampus [ 145 , 146 ].…”
Section: Neurobiology and Management Of Disease-associated Cognitive ...mentioning
confidence: 99%
“…In addition to the role of 5-HT 2A receptors in the treatment of cognitive deficit in schizophrenic patients, the role of other serotonin receptors has also been studied. Some atypical antipsychotic drugs, such as quetiapine or aripiprazole, stimulate 5-HT 1A receptors [135,136], providing an inhibitory feedback control of serotonin release in several areas of the brain [137]. This effect is related with an improvement in some cognitive functions such as verbal memory in schizophrenic patients, as seen with the 5-HT 1A agonist tandospirone [138].…”
Section: Modulation Of Serotonergic Neurotransmissionmentioning
confidence: 99%